Abilitas Komposit dalam Tes Potensi - Saifuddin Azwar; Ali Ridho (Jurnal Psikologi, 2013)
When a unidimensionality assumption has been actually violated, interpretation of test scores might be jeopardized. It couldn’t be overemphasized in case of high-stake exams such as PAPs UGM (academic potentiality test for UGM graduate student candidates) which was supposed to reflect a composite ability. This study aimed at revealing item characteristics of PAPs A-1 Series based on UIRT and MIRT and discovering dimensionality of the three subtests of the test. Scores of subject (n=2035) on the 3 subtests were analysed and the results showed that 27 items (10 of Verbal, 8 of Kuantitatif, and 9 of Penalaran) were flagged for having rbis of less than 0.25 and 6 other items for having abnormally high pseudo-guessing parameters. Dimensionality analyses found out that Penalaran subtest was local-dependent while Verbal and Kuantitatif subtests both were local-independent. In addition, MIRT analyses failed to fully describe item characteristics of the test due to effect of interaction among probabilities of correct response of the three subtests. Keywords: dimensionality, PAPs UGM, MIRT, UIRT